Tracking the Texas ranger historians - Glasrud, Bruce A.; Weiss, Harold J. Jr.; McCaslin, Richard B. (University of North Texas Press, 2024)
"The first systematic inquiry into the Texas Rangers did not begin until 1935 with Walter Prescott Webb's publication The Texas Rangers. Since then numerous works have appeared on the Rangers, but no volume has been published before that covers the various historians of the Rangers and their approaches to the topic. Editors Bruce A. Glasrud and Harold J. Weiss Jr. gather essays that profile individual historians of the Texas Rangers, explore themes and issues in Ranger history, and comprise archival research, biographies, and autobiographies. Several approaches in Texas historiography have influenced the writings on the Texas Rangers and serve to organize the chapters in the volume. Traditionalists (Chuck Parsons, Stephen L. Moore, and Bob Alexander) stress the revered happenings in the nineteenth century that brought about the Lone Star state and its empire-building Ranger force. To these historical writers the Texas Rangers were part of a golden age. Revisionists (Robert M. Utley, Louis R. Sadler, and Charles H. Harris) pull back from this adulation, emphasize the importance of overlooked ethnic and racial groups, and point out misbehavior on the part of Rangers. They also want to separate fact from fiction. Some Ranger historians (Frederick Wilkins and Mike Cox) straddle both traditional and revisionist approaches in their works. The final group, Cultural Constructionalists (Gary Clayton Anderson, Américo Paredes, and Monica Muñoz Martinez), continue the work of Revisionists and focus on an interconnected past that includes theoretical approaches and the study of memory and regional identities"--